Taxonomic notes on Encyclia (Orchidaceae, Epidendroideae): providing clarification about the small Encyclia bohnkiana - Oliveira, Marcos Da Conceição; Pacheco, Josélia Rozanny Vieira; Barberena, Felipe Fajardo V. A. (Phytotaxa, 2025)
We synonymize E. bohnkiana with E. thienii based on the analyses of protologues, illustrations, herbarium material, and field collections. We designate a lectotype for E. thienii and provide descriptions, taxonomic comments, photographs, and a distribution map of the species.